2007
DOI: 10.1016/j.jmwh.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lactation Risk for Late Preterm Infants and Mothers: Evidence and Management Strategies to Protect Breastfeeding

Abstract: Late preterm infants (34 0/7-36 6/7 weeks of gestation) are often cared for in general maternity units by clinicians who have limited experience with the specific needs of these newborns. Although the benefits of human milk are well documented, mothers and their late preterm infants are at risk for poor lactation outcomes. These include early breastfeeding cessation and lactation-associated morbidities, including poor growth, jaundice, and dehydration. Late preterm infants are more likely than term infants to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 59 publications
4
111
0
10
Order By: Relevance
“…NICU admission may improve breastfeeding rates in this population by providing: (1) the expertise to assess and support establishment of an adequate milk supply, via access to appropriate breast pumping supplies and information and (2) the expertise to assist in the breastfeeding in the neurologically immature infant, via International Board Certified Lactation Consult (IBCLC) and nursing providers accustomed to the breastfeeding challenges of prematurity. [33][34][35] Our study contains several limitations. The PRAMS instrument is self-administered and anonymous, making it impossible to validate the data collected at the subject level, excepting those data also collected as part of the birth certificate.…”
Section: Nicu Admission and Breastfeeding Prams 2000 To 2003mentioning
confidence: 99%
“…NICU admission may improve breastfeeding rates in this population by providing: (1) the expertise to assess and support establishment of an adequate milk supply, via access to appropriate breast pumping supplies and information and (2) the expertise to assist in the breastfeeding in the neurologically immature infant, via International Board Certified Lactation Consult (IBCLC) and nursing providers accustomed to the breastfeeding challenges of prematurity. [33][34][35] Our study contains several limitations. The PRAMS instrument is self-administered and anonymous, making it impossible to validate the data collected at the subject level, excepting those data also collected as part of the birth certificate.…”
Section: Nicu Admission and Breastfeeding Prams 2000 To 2003mentioning
confidence: 99%
“…25 The results suggest that participants, as a group, were not efficient breast-feeders and the shorter time held for breastfeeding may be an indication of poor endurance, a difficulty frequently highlighted in LPIs. 5,7,19 One explanation for poor endurance, may be the high rate of respiratory difficulties in this sample 26 (15% required oxygen at the time of evaluation and almost 50% had RDS). However, results indicated that more infants with RDS had breastfeeding sessions longer than 15 minutes, than infants without RDS.…”
Section: Resultsmentioning
confidence: 93%
“…8 Increased knowledge of specific breastfeeding characteristics may be useful in early identification, and intervention for breastfeeding difficulties that may place LPIs at risk for the negative cyclic implications that poor breastfeeding has on milk intake, infant physiological status, maternal anxiety and milk supply. 7,10,14,[17][18][19][20] The aim of this study was to further investigate the breastfeeding characteristics of LPIs receiving KMC. …”
Section: Reliability and Validitymentioning
confidence: 99%
“…A imaturidade neurológica e a falta de resposta a estímulos sensoriais presentes no prematuro justificam a presença de sucção fraca (22) .…”
Section: Discussionunclassified